Template-switching during DNA synthesis byThermus aquaticusDNA polymerase I - Shannon J. Odelberg; Robert B. Weiss; Akira Hata; R. White (1995)
Recombinant DNA molecules are often generated during the polymerase chain reaction (PCR) when partially homologous templates are available [e.g., see Pääbo et al . (1990) J. Biol. Chem. 265, 4718–4721]. It has been suggested that these recombinant molecules are a consequence of truncated extension products annealing to partially homologous templates on subsequent PCR cycles. However, we demonstrate here that recombinants can be generated during a single round of primer extension in the absence of subsequent heat denaturation, indicating that template-switching produces some of these recombinant molecules. Two types of template-switches were observed: (i) switches to pre-existing templates and (ii) switches to the complementary nascent strand. Recombination is reduced several fold when the complementary template strands are physically separated by attachment to streptavidln magnetic beads. This result supports the hypothesis that either the polymerase or at least one of the two extending strands switches templates during DNA synthesis and that Interaction between the complementary template strands Is necessary for efficient template-switching.